Determinants of Audit Quality in Manufacturing Companies in Indonesia - Rahman, Arif Nur; Achyani, Fatchan; Sasongko, Noer (Journal Research of Social Science, Economics, and Management, 2023)
This study was conducted to determine the effect of audit fees, audit tenure, client size, auditor rotation, gender of the audit committee chairman, expertise of the audit committee chairman, education of the audit committee chairman and tenure of the audit committee chairman on the audit quality of manufacturing companies listed on the Indonesia Stock Exchange in 2019-2022. The total sample in this study was 120 companies with sampling techniques using purposive sampling. This study uses logistic regression analysis with Eviews 10. The results of this study indicate that audit fees, audit tenure, client size, auditor rotation, audit committee chair expertise and audit committee chair education have no significant effect on audit quality in manufacturing companies. While the gender of the audit committee chairman has a negative and significant effect on audit quality in manufacturing companies, the tenure of the audit committee chairman has a positive and significant effect on audit quality in manufacturing companies. The results of this study imply the importance of internal company factors, especially the chairman of the audit committee in supervising the company in an effort to improve audit quality.